Peningkatan On Time Picking di PT. X Cabang Surabaya dengan menggunakan Metode Filosofi Six Sigma - Kevin Putra; Jani Rahardjo (Jurnal Titra, 2020)
Company X is a company which distributes pharmaceutical products such as medicines, medical devices, as well as consumary products including but not limited to milk, drinks, and snacks. The target for OTP that has been decided / agreed to by the company is 97.5%, but unfortunately the target has yet to be reached by Company X as it is currently standing at 84,78%To increase the percentage of the current OTP, the problems will be identified by using fishbone diagrams with 5-whys analysis. One of the major problem that has been identified is the scaterred goods. The writer suggests a solution using the six sigma philosophy. The six sigma philosophy produced a solution of using a handy talkie to a certain picker and to create a temporary staging transit. The solution yields an increase of 2.93% to the OTP.